Social Media Addiction and Adolescents: Relationship Between Social Media and Eating Behaviors During Pandemic - Gümüş, Damla; Sevim, Sümeyra; Kızıl, Mevlüde (Addicta: The Turkish Journal on Addictions, 2023)
The present study aimed to investigate the links between internet and social media usage, social media addiction, and eating behaviors of adolescents during coronavirus disease 2019 pandemic in Türkiye. A total number of 346 adolescents (243 girls and 103 boys) participated in the study. Daily internet, social media, and social media tools usage (h/day) were questioned. Participants completed the Social Media Addiction Scale for Adolescents for measurement of social media addiction and the Dutch Eating Behavior Questionnaire for investigation of eating behaviors. Daily internet and social media usage were found to be 6.1 ± 3.2 and 2.9 ± 2.2 hours, respectively, for boys and 6.0 ± 3.1 and 3.2 ± 2.3 hours, respectively, for girls. Social media addiction levels did not differ between genders, whereas the Dutch Eating Behavior Questionnaire and its subscales (emotional, external, and restrained eating) were statistically higher in girls (p < .001). The Social Media Addiction Scale for Adolescents was positively correlated with daily internet and social media usage duration, Dutch Eating Behavior Questionnaire, emotional eating, and external eating. Considering the potential interactions between social media and eating behavior, it is necessary to develop effective interventions regarding adolescents’ social media usage, eating behaviors, and attitudes.
Keywords: Adolescents; COVID-19; eating behavior; social media; social media addiction